2023
DOI: 10.3390/cells12121660
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Plasma Membrane Repair Therapeutics for Treating Neurodegenerative Diseases

Abstract: Plasma membrane repair is an essential cellular mechanism that reseals membrane disruptions after a variety of insults, and compromised repair capacity can contribute to the progression of many diseases. Neurodegenerative diseases are marked by membrane damage from many sources, reduced membrane integrity, elevated intracellular calcium concentrations, enhanced reactive oxygen species production, mitochondrial dysfunction, and widespread neuronal death. While the toxic intracellular effects of these changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…(7) Assessment of contributions to applied fields: Evaluation of the potential applications of research in this field, particularly in generating therapeutic medicine for the rapid recovery of diseases characterized by impaired wound repair, is necessary. Exogenous delivery of recombinant repair proteins such as MG53, annexins, or synthetic molecules has been shown to significantly enhance membrane repair in vivo and has proven effective for the treatment of muscular and neuronal damage [17,[228][229][230][231]. Additionally, the exploration of implications for developing agricultural fungicides is warranted.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…(7) Assessment of contributions to applied fields: Evaluation of the potential applications of research in this field, particularly in generating therapeutic medicine for the rapid recovery of diseases characterized by impaired wound repair, is necessary. Exogenous delivery of recombinant repair proteins such as MG53, annexins, or synthetic molecules has been shown to significantly enhance membrane repair in vivo and has proven effective for the treatment of muscular and neuronal damage [17,[228][229][230][231]. Additionally, the exploration of implications for developing agricultural fungicides is warranted.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Loss of the wound repair function is observed in various diseases, including diabetes [11], muscular dystrophies [12,13], acute kidney injury [14], and vitamin deficiencies [15]. Recent studies have identified defects in wound repair as common in Parkinson's and Alzheimer 's diseases [16][17][18]. Plant cells, affected by freezing damage in cold seasons, also possess the capability to repair damaged membranes [19][20][21].…”
Section: Introductionmentioning
confidence: 99%